Integrasi Geocapability dengan Contextual Learning (Kajian Kurikulum Pendidikan Geografi SMA di Banyuwangi) - Al Musafiri, M. Rizqon; Lathifatul Insaniyah, Anyes (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2025)
This study aims to examine the potential development of geocapability through a contextual learning approach within the Senior High School Geography curriculum, particularly in Banyuwangi Regency. The research focuses on analyzing the alignment between the concept of geocapability and the principles of contextual learning, as well as their implications for enhancing students' geographical competencies. This study adopts a qualitative approach using a literature review method. Data were collected from various sources, including academic journals, textbooks, curriculum documents, and related research. Data analysis was conducted through synthesis and interpretation processes to identify key themes and build a comprehensive argument.The findings indicate that integrating geocapability and contextual learning into the Senior High School Geography curriculum has the potential to improve students’ abilities in understanding and addressing complex geographical issues. The case study in Banyuwangi highlights the potential for applying this approach in a local context, considering the environmental and social characteristics of the community. The analysis shows that this approach can enhance student engagement, develop critical thinking skills, and strengthen the relevance of Geography learning. The integration of geocapability through contextual learning is an effective strategy for improving the quality of Geography education at the high school level. This study provides a conceptual and practical foundation for curriculum development aimed at enhancing students’ geographical capabilities. Recommendations for future research include empirical studies involving students and teachers to evaluate the effectiveness of implementation.